Smoking Ban and Small-For-Gestational Age Births in Ireland - Kabir, Zubair (Public Library of Science, 2013)
BACKGROUND: Ireland introduced a comprehensive workplace smoke-free legislation in March, 2004. Smoking-related adverse birth outcomes have both health care and societal cost implications. The main aim of this study was to determine the impact of the Irish smoke-free legislation on small-for-gestationa- age (SGA) births. METHODS AND FINDINGS: We developed a population-based birthweight (BW) percentile curve based on a recent study to compute SGA (BW <5(th) percentile) and very SGA (vSGA - BW<3(rd) percentile) for each gestational week. Monthly births born between January 1999 and December 2008 were analyzed linking with monthly maternal smoking rates from a large referral maternity university hospital. We ran individual control and CUSUM charts, with bootstrap simulations, to pinpoint the breakpoint for the impact of ban implementation ( = April 2004). Monthly SGA rates (%) before and after April 2004 was considered pre and post ban period births, respectively. Autocorrelation was tested using Durbin Watson (DW) statistic. Mixed models using a random intercept and a fixed effect were employed using SAS (v 9.2). A total of 588,997 singleton live-births born between January 1999 and December 2008 were analyzed. vSGA and SGA monthly rates declined from an average of 4.7% to 4.3% and from 6.9% to 6.6% before and after April 2004, respectively. No auto-correlation was detected (DW = ∼2). Adjusted mixed models indicated a significant decline in both vSGA and SGA rates immediately after the ban [(−5.3%; 95% CI −5.43% to −5.17%, p<0.0001) and (−0.45%; 95% CI: −0.7% to −0.19%, p<0.0007)], respectively. Significant gradual effects continued post the ban periods for vSGA and SGA rates, namely, −0.6% (p<0.0001) and −0.02% (p<0.0001), respectively. CONCLUSIONS: A significant reduction in small-for-gestational birth rates both immediately and sustained over the post-ban period, reinforces the mounting evidence of the positive health effect of a successful comprehensive smoke-free legislation in a vulnerable population group as pregnant women.